2013
DOI: 10.1002/ajim.22259
|View full text |Cite
|
Sign up to set email alerts
|

Roles of age, length of service and job in work‐related injury: A prospective study of 63,620 person‐years in female workers

Abstract: Younger and shorter lengths of service were at risk for various types of injuries. Higher length of service was at risk for injury due to materials/equipment/objects handling. Preventive measures should consider the respective risks associated with age, years of employment and job.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…There are several possible explanations for this result. Older workers possess lower physical work capacity due to a decrease in aerobic and musculoskeletal capacity [ 6 , 39 ]. Considering this, the management might have changed the older workers’ occupations into a relatively safe one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several possible explanations for this result. Older workers possess lower physical work capacity due to a decrease in aerobic and musculoskeletal capacity [ 6 , 39 ]. Considering this, the management might have changed the older workers’ occupations into a relatively safe one.…”
Section: Discussionmentioning
confidence: 99%
“…Margolis (2010) found that as age increases the number of days away from work following an injury also increases. However, Mitchell (1988) and Chau et al (2014) have shown that employees under the age of 25 rather than older ones are more likely to be injured [ 6 , 10 – 12 ]. Living habits (smoking and drinking) are observed to be significantly associated with injury events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of compensation data, which might provide some useful insights into reporting of MSDs, is challenging due to differences between countries in methods of data collection and socioeconomic differences (Farioli et al 2014) and the substantial influence of cultural beliefs on reporting of pain and discomfort (Coggon et al 2013). Some have reported that older workers are more likely to sustain fractures compared to sprains and strains than their younger counterparts (Algarni et al 2015), whilst others report younger workers are more likely to report injuries in general than their older colleagues (Chau et al 2014;Rohlman et al 2013). Evidence relating to time of work following injury is more consistent, with some agreement that once injured, older workers are more likely to be off work for longer than younger workers (Kiss et al 2008;Lötters and Burdorf 2006;Munk et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Work accidents and injuries are known to be multifactorial: Both individual and work-related factors play an important role in their occurrence. With regard to individual factors, previous studies generally showed that accidents and work in-jury absence occur more often in males as well as in younger, less experienced, and less educated workers [2][3][4][5][6] . Accidents and injuries are more prominent in construction, agriculture, and manufacturing sectors 7,8) as well as in small enterprises 9) .…”
Section: Introductionmentioning
confidence: 99%